Preparation of MOF-5 imprinted chromium ferrite and its application in decontaminating metronidazole and penicillin G contaminated water system - Babatunde K. Adeleke; Olamide A. Olalekan; Adewale Adewuyi; Woei Jye Lau; Olalere G. Adeyemi (Scientific Reports)
Abstract Metronidazole (MZ) and penicillin G (PG) are antibiotics frequently detected in aqueous systems as pollutants. Their presence in water systems is a global challenge requiring the development of sustainable solutions for water purification. Therefore, this study synthesized and improved the adsorption performance of chromium ferrite (CrFe2O4) via incorporation of metal-organic framework (MOF-5) to produce CrFe2O4@MOF-5 composite. CrFe2O4@MOF-5 and CrFe2O4 were characterized using a series of analytical instrument. Both adsorbents exhibited a four-phase mass loss from the thermogravimetric analysis, while the Brunauer-Emmett-Teller (BET) results gave a surface area of 40.94 m² g− 1 for CrFe2O4 and 59.76 m² g− 1 for CrFe2O4@MOF-5. Interestingly, microscopical images unfolded the surfaces of CrFe2O4@MOF-5 and CrFe2O4 to be heterogeneous, while elemental surface mapping confirmed the constituent elements of CrFe2O4@MOF-5 and CrFe2O4 to be Cr, Fe, O, C and Zn. CrFe2O4@MOF-5 exhibited a higher affinity (91.67 mg g− 1) for PG than CrFe2O4 (53.82 mg g− 1). Similarly, the performance of CrFe2O4@MOF-5 was better (90.24 mg g− 1) compared to CrFe2O4 (50.41 mg g− 1) towards MZ. Both Freundlich and Langmuir isotherm may describe the removal process of MZ and PG by CrFe2O4@MOF-5 while sorption of MZ and PG by CrFe2O4 fitted best for Langmuir isotherm in a sorption mechanism involving electrostatic interaction and pore diffusion. The adsorption performance of CrFe2O4@MOF-5 and its regeneration capacity compared agreeably with most published adsorbents in literature. This current study showed CrFe2O4@MOF-5 as a potential adsorbent for decontaminating MZ and PG-polluted water systems.